High-flow nasal cannula oxygen therapy in infants and children versus other non-invasive ventilation: a review of current knowledge - Mahmoud Hassan Mahmoud Elmakkawy, Mariam; Nunis, Melissa Anne; Zainudin, Zurina; Mohamed Nashrudin, Khairoon Nisa; Ellias, Mohd Fahmi; Gad, Safwat Hassan (Ecronicon, 2024)
Respiratory distress is the leading cause of hospitalisation in paediatric intensive care units. Non-invasive ventilation can be delivered via continuous positive airway pressure (CPAP), bilevel positive airway pressure (BiPAP) or high-flow nasal cannula (HFNC). HFNC protocols are based only on manufacturers’ studies, with positive nasopharyngeal pressure as the primary endpoint. These protocols recommend the use of humidified air to prevent irritation of the airway mucosa. HFNC therapy may be better tolerated than traditional modes of non-invasive support, such CPAP and BiPAP in part owing to its smaller nasal prong interface allowing activities like breastfeeding with greater ease